2001
DOI: 10.1097/00005768-200102000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Leg power and hopping stiffness: relationship with sprint running performance

Abstract: Although muscle power is needed for acceleration and maintaining a maximal velocity in sprint performance, high leg stiffness may be needed for high running speed. The ability to produce a stiff rebound during the maximal running velocity could be explored by measuring the stiffness of a rebound during a vertical jump.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
193
3
18

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(232 citation statements)
references
References 28 publications
18
193
3
18
Order By: Relevance
“…The data obtained in this study support the results of the previous ones which have found a negative relationship between surface compliance and oxygen consumption [1,2,9]. It has been proposed that a compliant elastic surface will passively store and return energy with each step, reducing the mechanical work performed by the runner's muscles [22].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data obtained in this study support the results of the previous ones which have found a negative relationship between surface compliance and oxygen consumption [1,2,9]. It has been proposed that a compliant elastic surface will passively store and return energy with each step, reducing the mechanical work performed by the runner's muscles [22].…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the studies have revealed that an increase in leg stiffness enhances running speed [7][8][9]20,27] or jumping performance [1][2][3]8,16,18,19]. Leg stiffness was also found to be associated with running economy, as measured by oxygen consumption, [17,26,30].…”
Section: Discussionmentioning
confidence: 99%
“…171 The pervasive role of eccentric muscular force enhancement prior to a power activity (eg, during a SSC) may be the most substantial during high-power sport activities such as running, 31,35 sprinting, 40,60,129 hopping, 40,115 and jumping. 22,115,153 The importance of the SSC in almost all sport activities (possible exceptions being bicycling and swimming) cannot be overstated.…”
Section: Eccentric Contractions: Structural and Functional Changes Tomentioning
confidence: 99%
“…The leg spring is compressed during the first half of the stance phase and rebounds during the second half. The stiffness of the leg spring or leg stiffness (K leg , defined as the ratio of maximal ground reaction force to maximum leg compression at the middle of the stance phase) has been shown to correlate with sprint ability in sprinters, and handball and tennis players [19][20][21] .…”
Section: Leg Stiffness During Hopping and Runningmentioning
confidence: 99%